Pola Komunikasi Dan Respon Pegawai Terhadap Upaya Peningkatan Semangat Kerja Di Institut Agama Islam Negeri (Iain) Kediri - Siti Amanah (Happiness: Journal of Psychology and Islamic Science, 2022)
This study describes and analyzes: (1) organizational communication patterns built by employees towards efforts to increase morale at IAIN Kediri (2) Employee responses (related to providing direction, supervision, education and training, performance appraisal and opportunities given to subordinates in express opinions) on efforts to increase morale at IAIN Kediri. This research is a type of descriptive qualitative research with informants consisting of leaders of IAIN Kediri, Dean of Faculties at IAIN Kediri, Deputy Deans, Head of Study Programs, Heads of Subdivisions, certain unit officials, lecturers to educational staff (employees) in IAIN Kediri. The data used in this study are primary data and secondary data with data collection techniques of observation, in-depth interviews and documentation. The data analysis used is the Miles and Huberman interactive data analysis model which includes: data reduction, data presentation as well as drawing conclusions and verification. Based on the results of the study, it can be concluded that: (1) The pattern of organizational communication built between leaders and subordinates towards efforts to increase morale at IAIN Kediri is to apply organizational communication flows that include vertical and horizontal communication flows. In addition, formal communication through coordination meetings and informal communication such as sharing or even through social media is also enforced. (2) Employee responses show varied results towards efforts to increase morale in terms of direction, supervision, performance appraisal, education and training and the provision of morale. In this case, the leader does not shut down and accepts different thoughts and responses